Treatment of critically ill COVID-19 patients: practical guidelines - Stevanović, Predrag (Medicinski podmladak, 2021)
The coronavirus disease pandemic (2019) has burdened health systems around the world with a large number of severe patients in a short period of time. According to the law of large numbers, a significant number of critically ill Covid-19 patients appear in such conditions, who require treatment in the intensive care unit. That percentage is around 3-5% in different countries. It is similar in Serbia, however, every rule has exceptions. KBC "Dr Dragiša Mišović-Dedinje" in Belgrade has been determined to take care of the most difficult Covid-19 patients since the beginning of the epidemic due to space, organizational and personnel possibilities. Out of the total number of patients treated in KBC Mišović, about 25% of patients were treated in the intensive care unit for the previous reasons. Guided by valid treatment protocols, Anesthesiology and Intensive Care clinic of the CHC Mišović has developed its own work protocols for rapid diagnosis, isolation and clinical management of such difficult patients. These protocols are important not only for the treatment of the most severe Covid-19 patients, but also for the best utilization of hospital resources, as well as for the prevention of the spread of the infection to the medical staff. Extensive experience in the treatment of critically ill patients was gained from the entire engagement during the epidemic, experienced doctors, anesthesiologists-intensivists with great knowledge in the field of work in the intensive care unit, but also managers of clinics and institutions, who can share their experience to health care policy makers. It is clear that in the future, the capacities and organization of work in the field of intensive care medicine should be redefined, as well as health workers should be trained to work in this, the most demanding field of medicine. Expert experience in the form of practical guidelines, derived from over fourteen months of continuous work in the red zone of Covid, where they fought for every breath of the patient, in this review are translated into simplified guidelines for orientation to those who find themselves in a similar situation.